TECHNICAL ANALYSIS OF RIGID PAVEMENT AND FLEXIBLE PAVEMENT CALCULATIONS ON TEUKU UMAR ROAD – RAJAWALI ROAD - Budiyanto, Arief; Muhammadun, Haris; Marleno, Risma (INTERNATIONAL JOURNAL ON ADVANCED TECHNOLOGY, ENGINEERING, AND INFORMATION SYSTEM, 2024)
Road development in Sampang Regency is carried out based on the Vision and Mission of the 2019-2024 RPJMD, as stated in Mission point 3 Infrastructure: "Improving Quality and Sustainable Infrastructure Development." In 2023, the Sampang Regency Public Works and Spatial Planning Office reported that road stability was at 46.54% of the total length of 754.12 km of district roads. This research on the Teuku Umar Road - Rajawali Road Preservation project aims to analyze the calculation of rigid pavement construction thickness planning for a design life of 20 years, and flexible pavement construction using the Road Pavement Design Manual No. 02/M/BM/2017 method. The analysis of calculations for both rigid and flexible pavements uses the Road Pavement Design Manual Method No. 02/M/BM/2017 for a design life of 20 years. The results of this research indicate that the rigid pavement design includes 200 mm thick concrete, 100 mm skinny concrete, and 150 mm class A aggregate LPA. For the flexible pavement, the design includes 40 mm AC-WC Laston, 60 mm AC-BC Laston, and 400 mm class A aggregate LPA.